Does campylobacter jejuni form biofilms in food-related environments? - Teh, A.; Lee, S.; Dykes, Gary (2014)
Campylobacter jejuni is one of the most frequent causes of bacterial gastrointestinal food-borne infection worldwide. This species is part of the normal flora of the gastrointestinal tracts of animals used for food production, including poultry, which is regarded as the primary source of human Campylobacter infections. The survival and persistence of C. jejuni in food processing environments, especially in poultry processing plants, represent significant risk factors that contribute to the spread of this pathogen through the food chain. Compared to other food-borne pathogens, C. jejuni is more fastidious in its growth requirements and is very susceptible to various environmental stressors. Biofilm formation is suggested to play a significant role in the survival of C. jejuni in the food production and processing environment. The aims of this minireview were (i) to examine the evidence that C. jejuni forms biofilms and (ii) to establish the extent to which reported and largely laboratory-based studies of C. jejuni biofilms provide evidence for biofilm formation by this pathogen in food processing environments. Overall existing studies do not provide strong evidence for biofilm formation (as usually defined) by most C. jejuni strains in food-related environments under the combined conditions of atmosphere, temperature, and shear that they are likely to encounter. Simple attachment to and survival on surfaces and in existing biofilms of other species are far more likely to contribute to C. jejuni survival in food-related environments based on our current understanding of this species.